1991
DOI: 10.1203/00006450-199105010-00017
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Nifedipine in Children with Bronchopulmonary Dysplasia and Pulmonary Hypertension

Abstract: ABSTRACT. The pharmacokinetics and associated pharmacodynamics of nifedipine were studied in nine children aged 5 to 68 mo with bronchopulmonary dysplasia and pulmonary artery hypertension after a single oral dose of 1.44 tLmol/kg (0.5 rug/kg). In the cardiac catheterization laboratory, hemodynamic measurements were made in duplicate just before the nifedipine dose and at 5 min and 0.5 and 1.0 h after the dose. The plasma nifedipine concentration was measured by HPLC at each of the above times and at 2.5, 4.0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…279,281,282 Nifedipine can acutely lower PAP and PVR in children with BPD, but the effects of nifedipine on PAP were not different from the effects of supplemental oxygen alone. Compared with a short-term study of iNO reactivity in BPD, the acute response to CCB was poor, and some infants developed systemic hypotension.…”
Section: Treatmentmentioning
confidence: 99%
“…279,281,282 Nifedipine can acutely lower PAP and PVR in children with BPD, but the effects of nifedipine on PAP were not different from the effects of supplemental oxygen alone. Compared with a short-term study of iNO reactivity in BPD, the acute response to CCB was poor, and some infants developed systemic hypotension.…”
Section: Treatmentmentioning
confidence: 99%
“…Other investigators demonstrated improvement in PVR in patients with BPD and PAH in response to prostacyclin 12,20 and variable responsiveness to calcium channel blockers. 6,30 Evaluation of PAH in Infants With BPD The prevalence of and risk factors for PAH in infants with BPD are not known, which complicates the development of an effective screening strategy. In the present study, almost one half of the 18 patients with systemic or suprasystemic RV pressure were SGA, which suggests that SGA infants may be at increased risk for severe PAH.…”
Section: Anatomic and Functional Factors Contributing To Pah In Infanmentioning
confidence: 99%
“…In this regard, calcium channel blockers (CCBs) have been used as long-term vasodilator therapies for PAH in the pediatric population that responds positively to an acute vasodilator test (4,30,32). The CCBs exert their vasodilator effect by binding with high affinity to long-lasting or "L-type" calcium (Ca L ) channels in vascular smooth muscle cells (VSMCs) to attenuate voltage-gated Ca 2ϩ influx.…”
mentioning
confidence: 99%